Transcendence and Religion - Borg, Meerten B. ter (Implicit religion, 2008)
This essay deals with the relationship between religion, both implicit and explicit, and transcendence. The starting point is Thomas Luckmann's idea that man is a religious animal. After all, it is necessary for human beings to transcend their biological habitus in order to survive. It is suggested that transcendence is a necessary, rather than a sufficient precondition for religion.